Optimalisasi Edukasi Dampak Dan Pencegahan Pernikahan Dini Melalui Media Video Di SMPIT Al-Adzkia Sentul Tembelang Jombang - Purwanti, Rosa (Pakis Journal Institute, 2024)
Early marriage in Indonesia states that the minimum age for marriage is under 19 years old for men and women. Early marriage has an impact ranging from the risk of stunted babies, maternal and infant deaths, health problems, disharmonious marriages, to aspects of education and self-development that are hampered, even triggering domestic violence and poverty. The method used for education about early marriage at SMPIT Al-Adzkia Sentul Tembelang Jombang. is by providing Health Education about the impact of early marriage through educational video media. Community service activities ran in an orderly and smooth manner, showing that there was an increase in students' understanding of the impact of early marriage after being treated with 50 students with a percentage of 77%-82%, compared to before participating in group guidance where the level of student understanding was in the low category with a percentage of 40%-55% each. Participants in community service activities were ± 50 people. Participants were very enthusiastic and communicative with the speakers. Conclusion: Education about early marriage needs to continue to be carried out continuously by involving students, teachers, parents and the surrounding community to create a family/home environment, schools and communities so that it can reduce the rate of early marriage.